Menthol response and adaptation in nociceptive-like and nonnociceptive-like neurons: role of protein kinases - Sarria Ignacio; Gu Jianguo (SAGE Publishing, 2010)
Abstract Menthol-sensitive/capsaicin-insensitive neurons (MS/CI) and menthol-sensitive/capsaicin-sensitive neurons (MS/CS) are thought to represent two functionally distinct populations of cold-sensing neurons that use TRPM8 receptors to convey innocuous and noxious cold information respectively. However, TRPM8-mediated responses have not been well characterized in these two neuron populations. Using rat dorsal root ganglion neurons, here we show that MS/CI neurons had larger menthol responses with greater adaptation. In contrast, MS/CS neurons had smaller menthol responses with less adaptation. All menthol-sensitive neurons showed significant reduction of menthol responses following the treatment of cells with the protein kinase C (PKC) activator PDBu (Phorbol 12,13-dibutyrate). PDBu-induced reduction of menthol responses was completely abolished in the presence of PKC inhibitors BIM (bisindolylmaleimide) or staurosporine. When menthol responses were examined in the presence of protein kinase inhibitors, it was found that the adaptation was significantly attenuated by either BIM or staurosporine and also by the Ca2+/calmodulin-dependent protein kinase (CamKII) inhibitor KN62 (N,O-bis(5-isoquinolinesulfonyl)-N-methyl-L-tyrosyl]-4-phenylpiperazine) in MS/CI neurons. In contrast, in MS/CS neurons menthol response was not affected significantly by BIM, staurosporine or KN62. In both MS/CI and MS/CS neurons, the menthol responses were not affected by PKA activators forskolin and 8-Br-cAMP (8-Bromoadenosine-3', 5'-cyclic monophosphate) or by protein kinase A (PKA) inhibitor Rp-cAMPs (Rp-Adenosine-3',5'-cyclic monophosphorothioate). Taken together, these results suggest that TRPM8-mediated responses are significantly different between non-nociceptive-like and nociceptive-like neurons.